Genetic variants of RNASE3 (ECP) and susceptibility to severe malaria in Senegalese population - Gora Diop; Céline Derbois; Cheikh Loucoubar; Babacar Mbengue; Bineta Niakhana Ndao; Fatou Thiam; Alassane Thiam; Rokhaya Ndiaye; Yakhya Dieye; Robert Olaso; Jean-Francois Deleuze; Alioune Dieye (Malaria Journal, 2018)
Abstract Background Severe forms of malaria (SM) are an outcome of Plasmodium falciparum infection and can cause death especially in children under 4 years of age. RNASE3 (ECP) has been identified as an inhibitor of Plasmodium parasites growth in vitro, and genetic analysis in hospitalized Ghanaian subjects has revealed the RNASE3 +371G/C (rs2073342) polymorphism as a susceptibility factor for cerebral malaria. The +371 C allele results in an Arg/Thr mutation that abolishes the cytotoxic activity of the ECP protein. The present study aims to investigate RNASE3 gene polymorphisms and their putative link to severe malaria in a malaria cohort from Senegal. Methods/results Patients enrolled from hospitals were classified as having either uncomplicated (UM) or severe malaria (SM). The analysis of the RNASE3 gene polymorphisms was performed in 241 subjects: 178 falciparum infected (96 SM, 82 UM) and 63 non-infected subjects as population control group (CTR). Six frequent SNPs (MAF > 3%) were identified, and one SNP was associated with malaria severity by performing a logistic regression analysis SM vs.UM: RNASE3 +499G/C (rs2233860) under age, sex as covariates and HbS/HbC polymorphisms adjustment (p = 0.003, OR 0.43, CI 95% 0.20–0.92). The polymorphisms: +371G/C (rs2073342), +499G/C (rs2233860) and +577A/T (rs8019343) defined a haplotype risk (G-G-T) for malaria severity (Fisher exact test, p = 0.03) (OR 4.1, IC 95% (1.1–14.9). Conclusion In addition to the previously described association of +371G/C polymorphism in Ghanaians cohort, the RNASE3 +499G/C polymorphism was associated with susceptibility to SM in a Senegalese population. The haplotype +371G/+499G/+577T defined by RNASE3 polymorphisms was associated with severity. The genetic association identified independently in the Senegalese population provide additional evidence of a role of RNASE3 (ECP) in malaria severity.